Viral Da’wah Content (Case Study of Ustadzah Oki Setiana Dewi's Da'wah Concerning Domestic Violence) - Nisa, Amalia; Alkaromi, Diemas Wildan; Amilah, Atina Nur; Puspitasari, Varya (Institut Agama Islam Negeri Parepare, 2023)
The digital era in conveying da'wah messages is not only conveyed directly but can also be done visually through social media, so there is a big possibility that it will go viral in society. The aim of this research is to identify and analyze why and how the causes of viral preaching content about domestic violence (domestic violence) conveyed by a preacher on social media, namely Ustadzah Oki Setiana Dewi. The research method used is a qualitative method with data collection techniques through observation and documentation. The results of the research found that the viral content was a snippet from Ustadzah Oki Setiana Dewi's lecture, the words used by the preacher caused the audience to think that acts of domestic violence were considered normal